A Case Study Of Ayurvedic Management Of Gridhrasi W.S.R. To Sciatica - Meena, Seema; Sharma, Ravi (International Research Journal of Ayurveda & Yoga, 2021)
Gridhrasi is one of the “Nanatmaja Vyadhis :of vata”. Improper sitting postures continuous and over exertion, jerking movements during travelling and sports produce structural abnormality in spinal cord. Vata is the prime dosha in the causation of Gridhrasi. The vitiated vata dosha get localized in the sphik, kati region. Occasionally it will be associated with kapha producing vata kaphaj Gridhrasi. Gridhrasi is pain dominant vyadhi so it causes major discomfort to the patient. Pain originates in lumbosacral region and radiate down to tip of legs through posterior aspects of thigh, knee and calf region. Sciatica nerve compression is the main cause of this. Pain creating a major discomfort to the patients. Gridhrasi is cured by the help of shamana chikitsa. Hence in the case study of male patient of age 48 yrs presenting with cardinal clinical sign and symptoms of Gridhrasi are Ruka, Toda, Stambha and Muhu Spandana in the Sphika, Kati, Uru,Janu, Jangha and Pad in order and Sakthikshepanigraha that is restricted lifting of the leg.